Network Security Analysis on The Internet Facility (Wifi) UIN Syarif Hidayatullah Jakarta Against Packet Sniffing Attacks - Anwar, A. Nurul (Institut Riset dan Publikasi Indonesia, 2024)
In an increasingly digital era, network security has become very important to protect sensitive data from cyber attacks. One common attack is a packet sniffing attack, where hackers can capture and snoop on data packets sent over a WiFi network. This research aims to analyze the level of network security in internet facilities (WiFi) at UIN Syarif Hidayatullah Jakarta against packet sniffing attacks. The methods used include surveys, observations and technical analysis of existing network infrastructure. The research results show that although UIN Syarif Hidayatullah Jakarta has implemented several network security measures, there are still gaps that can be exploited by packet sniffing attacks. Factors such as the use of vulnerable network protocols and lack of use of data encryption are the main causes of network vulnerability to these attacks. Recommendations include the implementation of additional security measures such as the use of more secure protocols, implementation of strong data encryption, as well as user training and awareness to minimize the risk of packet sniffing attacks. In this way, it is hoped that internet facilities (WiFi) at UIN Syarif Hidayatullah Jakarta can be safer and protected from potentially detrimental cyber attacks.